2011
DOI: 10.1504/ijspm.2011.048007
|View full text |Cite
|
Sign up to set email alerts
|

Industrial workstations design: a real case study

Abstract: The research work advances the effective design of the most critical workstations belonging to a real industrial plant; to this end, the authors propose an approach based on the integration of Modeling & Simulation tools, several ergonomic standards and the most known work measurement tools. The Modeling and simulation tools allow to implement a three-dimensional environment capable of recreating, with satisfactory accuracy, the evolution over the time of the real workstations. The ergonomic standards consent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The authors already carried out research activities (in cooperation with the same manufacturing system) on workstation ergonomic effective design 72 and production planning and control. 73 A brief description of the operations performed in each workstation of the industrial plant is reported below.…”
Section: Application Of the General Framework For Manufacturing Womentioning
confidence: 99%
“…The authors already carried out research activities (in cooperation with the same manufacturing system) on workstation ergonomic effective design 72 and production planning and control. 73 A brief description of the operations performed in each workstation of the industrial plant is reported below.…”
Section: Application Of the General Framework For Manufacturing Womentioning
confidence: 99%